PENGARUH KOMITE AUDIT, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN UMUR PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Irna; Edi Sutanto; Nurhaini; Ana Ima Sofana (The Asia Pacific Journal Of Management Studies, 2025)
This research aims to determine the influence of the audit committee and company size on earnings management with company age as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. There are two independent variables (X) in this research, namely Audit Committee (X1) and Company Size (X2), the dependent variable is Earnings Management (Y) and the Moderating variable is Company Age (W). The population in this study was 166 companies in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique used was Purposive Sampling. The number of samples used in this research was 52 companies based on certain criteria. This type of research is quantitative research and the data source used is secondary data using data collection methods, namely annual reports and company financial reports. The analysis technique used in this research is moderated regression analysis and processed using SPSS version 23 software. Based on the results of the analysis and hypothesis testing in this research, it can be concluded that the Audit Committee partially has a significant and significant influence on Profit Management, Company Size partially has no and significant effect on Profit Management, Company Age is partially unable to moderate the influence of the Audit Committee on Profit Management, Company Age is able to moderate the Influence of Company Size on Profit Management.